Pengetahuan, Sikap, dan Praktik Mengenai Stroke Akut dan Trombolisis pada Pasien Rawat Jalan Rumah Sakit Tersier di Medan, Indonesia: Studi Potong Lintang - Stephanie Salim; Kezia Sandria Lovely Tambunan; Mariska Mariska (Fakultas Kedokteran Universitas Trisakti, 2026)
Background Stroke is a leading cause of premature death globally, and Indonesia has a high prevalence of stroke at 10.9 per 1,000 individuals. Although thrombolytic therapy (rt-PA) is highly effective when administerd within golden period of 4,5 hours. Despite the effectiveness of thrombolytic therapy (rt-PA), its use in Indonesia remains low (<10%) due to significant knowledge gaps. Objectives This study assesses knowledge, attitudes, and practices (KAP) regarding acute stroke and thrombolysis among hospital outpatients. Methods A cross-sectional study was conducted at Hermina Hospital Medan (November 2024–February 2025) with 129 respondents. KAP scores were converted to a 0–100% scale. Differences were analyzed using Mann–Whitney U and Kruskal–Wallis H tests, and relationships were assessed using Spearman’s rho correlation (rs) because the data were not normally distributed. Results Adequate stroke knowledge was reported by 49.6% of respondents, but only 17.8% recognized thrombolysis as a specific stroke therapy. Educational level significantly influenced total KAP scores (p=0.000). Significant positive correlations were observed between knowledge and attitude (rs=0.479, p<0.001) and between knowledge and practice (rs=0.425, p<0.001). Conclusions While outpatients have moderate knowledge, a significant action gap remains, particularly regarding thrombolytic treatment and emergency response. Targeted education for low-literacy groups is essential to improve stroke outcomes.